PENGEMBANGAN EVALUASI AFEKTIF MATA KULIAH PENDIDIKAN AGAMA ISLAM - MAMI HAJAROH (Universitas Negeri Yogyakarta, 2006)
Abstract The aims of this research is to develop an affective evaluation models and to produce its evaluation instrument in the course of Education on Islam religion for students of D-II Elementary School Teachers Education so that there will be a qualified standard of non-test instrument. This research is a development research study with population consisting of students of D-II elementary School Teachers Education of Yogyakarta State University of 2004/2005 academic year who took the course on education of Islam religion. The sample was selected purposively involving classes N.15 and D.15 class. The development research followed the research steps: 1) Preparation; 2) Construction of an affective evaluation; 3) Models try out; 4) Model analysis; 5) Evaluation and reflection. Analyze data involve the use of statistic parametric with factor analysis. The data analysis employing the SPSS Program shows that, from 50 items in the effective evaluation instrument on education of Islam religion, 8 items are invalid because their F value are smaller than 0.3 and 4 items are invalid because F values are negative. From the eigenvalue with F values greater than 1 as F values that can be used as a factor of a traits,the affective evaluation instrument for Education of islam comprised 28 faktors with a cumulative percentage 90.27%. from the statistical figure, it can be conclude that the affective evaluation instrument for Education instrument for Education of Islam religion can be used as an affective evaluation instrument. The Cronbach alpha reliability coefficient is 0.7. therefore, this instrument is reliable enough to measure an affective aspect in Education of islam. Keywords: evaluation, affective, education of Islam religion